2020
DOI: 10.1080/20013078.2020.1800979
|View full text |Cite
|
Sign up to set email alerts
|

Increased small extracellular vesicle secretion after chemotherapy via upregulation of cholesterol metabolism in acute myeloid leukaemia

Abstract: Most patients with acute myeloid leukaemia (AML) experience disease recurrence after chemotherapy largely due to the development of drug resistance. Small extracellular vesicles (sEVs) are known to play a significant role in leukaemia drug resistance by delivery of antiapoptotic proteins and genes conferring resistance to recipient cells. sEV levels are elevated in AML patients' plasma at the time of diagnosis and remain elevated in complete remission after chemotherapy. The mechanism of enhanced sEV secretion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 33 publications
0
27
0
Order By: Relevance
“…4 j–m). Recent evidence suggests that chemotherapy can enhance HMGCR protein levels in the context of acute myeloid leukemia (AML) such that statins may represent effective anticancer treatments [ 27 , 28 ]. We therefore assessed HMGCR protein levels via Western blotting and found that these levels were significantly elevated 12 h following MPPa-PDT relative to other treatment groups (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4 j–m). Recent evidence suggests that chemotherapy can enhance HMGCR protein levels in the context of acute myeloid leukemia (AML) such that statins may represent effective anticancer treatments [ 27 , 28 ]. We therefore assessed HMGCR protein levels via Western blotting and found that these levels were significantly elevated 12 h following MPPa-PDT relative to other treatment groups (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Chemotherapy-induced alterations in the relationship between EVs and cholesterol transfer was recently studied in acute myeloid leukemia (AML) [ 48 ]. AML cells were shown to increase cholesterol levels and secrete a significantly greater number of EVs containing HMG-CoA reductase (HMGCR) after treatment with cytarabine.…”
Section: Ev-driven Communication In the Tumor Microenvironmentmentioning
confidence: 99%
“…3 A). High levels of cholesterol could negatively regulate the immune system, for example thorough inhibition of sterol regulatory element-binding proteins in NK cells, leading to dysfunction in anti-tumor immunity and development of chemoresistance [ 48 , 49 ].
Fig.
…”
Section: Ev-driven Communication In the Tumor Microenvironmentmentioning
confidence: 99%
“…Small-sized endothelial microparticles (sEMPs) in plasma decreased after chemotherapy and were associated with better prognoses of breast cancer patients [92]. In contrast, the levels of small extracellular vesicles (sEVs) in acute myeloid leukaemia remained high after chemotherapy, predicting possible therapy resistance [93]. Furthermore, the dynamic concentration alterations in EVs during therapy also suggest disease progression [13,84] and lower EV concentrations after NAC suggest the possible presence of minimal residual disease [13].…”
Section: Outstanding Questionsmentioning
confidence: 99%